THERMODYNAMICS OF CHEMICAL PROCESSES OF PHOSPHORUS ALLOCATION DURING THE PROCESS OF MELTING IN STEEL-MAKING FURNACES - V. F. Sobolev; A. A. Chichko; N. V. Andrianov; M. A. Murikov (Литьë и металлургия)
The analysis of thermodynamic models, which can be used for calculation of phosphorus allocation in the process of melting in steel-making furnace, is presented. It is shown, that temperature of melting process, basic capacity and oxidability of slag mixture in furnace influence to a greatest extent on allocation of phosphorus.